The Role of Audit Quality in Limiting Creative Accounting Techniques in Syrian Shareholding Companies: Field Study" - عبد الحليم مريم (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aims to clarify the role of Audit Quality in Limiting Creative Accounting Techniques in Syrian Shareholding Companies. To achieve the objective of this research, a field study was conducted by using a questionnaire to collect data from the population of the study which is composed of auditors accredited by the Finance Ministry, and authorized to audit shareholding companies. The questionnaire was distributed to 489 out of 493 auditors. 124 copies were returned, and 109 of them were suitable for analysis. The study concluded that Syrian shareholding companies implement techniques of creative accounting in varying rates. The study showed that the external auditor does pay enough attention in reaching a high level of quality that ensures the reduation of creative accounting in Syrian shareholding companies.